(untitled) (Лучшие интеллектуальные исследования, 2024)
This article discusses the modern methods of treating adenoid gland vegetation in children, focusing on both conservative and surgical approaches. It explores the clinical features, diagnostic techniques, and treatment strategies for adenoid hypertrophy, highlighting the importance of early detection. The article also examines innovative therapies such as laser treatment, cryotherapy, and endoscopic adenoidectomy, comparing their effectiveness in managing adenoid-related symptoms. Additionally, the article provides recommendations for improving the quality of life for children suffering from adenoid vegetation, emphasizing the significance of individualized treatment plans based on the severity of the condition.